(untitled) (Journal of Imam Al-Kadhim College, 2024)
The research reviews economic diplomacy as a concept that includes multiple activities and fields that rely on economic tools. It has become a major influence in international interactions through many international actors, as it is a vital tool for achieving economic and political interests at the international level, which includes countries and international organizations concerned with economic affairs, as well as About multinational companies, Which would contribute to enhancing international trade, attracting investments, and creating many economic arrangements, as economic diplomacy is an effective tool in enhancing international interactions, especially as represented by the roles of actors that are limited to states over other actors .While highlighting the Chinese experience as an important model for the study, which has demonstrated its effectiveness in utilizing its economic power and enhancing its influence in the world, the research has come up with recommendations for creating comprehensive institutional arrangements to ensure the achievement of justice and in an effort to create a platform for permanent dialogue and avoid crises in the future.